Target enrichment of ultraconserved elements from arthropods provides a genomic perspective on relationships among Hymenoptera. (29th September 2014) - Faircloth, Brant C.; Branstetter, Michael G.; White, Noor D.; Brady, Seán G.
Abstract Gaining a genomic perspective on phylogeny requires the collection of data from many putatively independent loci across the genome. Among insects, an increasingly common approach to collecting this class of data involves transcriptome sequencing, because few insects have high‐quality genome sequences available; assembling new genomes remains a limiting factor; the transcribed portion of the genome is a reasonable, reduced subset of the genome to target; and the data collected from transcribed portions of the genome are similar in composition to the types of data with which biologists have traditionally worked (e.g. exons). However, molecular techniques requiring RNA as a template, including transcriptome sequencing, are limited to using very high‐quality source materials, which are often unavailable from a large proportion of biologically important insect samples. Recent research suggests that DNA‐based target enrichment of conserved genomic elements offers another path to collecting phylogenomic data across insect taxa, provided that conserved elements are present in and can be collected from insect genomes. Here, we identify a large set (n = 1510) of ultraconserved elements (UCEs) shared among the insect order Hymenoptera. We used in silico analyses to show that these loci accurately reconstruct relationships among genome‐enabled hymenoptera, and we designed a set of RNA baits (n = 2749) for enriching these loci that researchers can use with DNA templates extracted from a variety of sources. We used our UCE bait set to enrich an average of 721 UCE loci from 30 hymenopteran taxa, and we used these UCE loci to reconstruct phylogenetic relationships spanning very old (≥220 Ma) to very young (≤1 Ma) divergences among hymenopteran lineages. In contrast to a recent study addressing hymenopteran phylogeny using transcriptome data, we found ants to be sister to all remaining aculeate lineages with complete support, although this result could be explained by factors such as taxon sampling. We discuss this approach and our results in the context of elucidating the evolutionary history of one of the most diverse and speciose animal orders.